2018
DOI: 10.1128/jvi.01970-17
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Live Influenza Vaccine Priming Elicits Localized B Cell Responses in Mediastinal Lymph Nodes

Abstract: Pandemic live attenuated influenza vaccines (pLAIV) prime subjects for a robust neutralizing antibody response upon subsequent administration of a pandemic inactivated subunit vaccine (pISV). However, a difference was not detected in H5-specific memory B cells in the peripheral blood between pLAIV-primed and unprimed subjects prior to pISV boost. To investigate the mechanism underlying pLAIV priming, we vaccinated groups of 12 African green monkeys (AGMs) with H5N1 pISV or pLAIV alone or H5N1 pLAIV followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 67 publications
(107 reference statements)
6
33
0
Order By: Relevance
“…Using a fluorescent stabilized stem immunogen (27), we determined that most, if not all, H5 + H1 + double-positive cells bound the HA stem while the H5 + single-positive cells did not (Supplemental Figure 1B). AGMs vaccinated with H5N1 pLAIV showed a small but detectable population of H5 + H1 + double-positive stem-specific memory B cells in the peripheral blood ( Figure 1, A and B) and MLNs at day 14 ( Figure 1C), but, as previously reported (21), the frequency of H5 + head-specific memory B cells was markedly higher in both the peripheral blood and MLNs at day 14 after pLAIV (0.05%-0.19% and 0.21%-0.64% for stem-and head-specific frequencies in the MLN, respectively). Consistent with these findings and our previous reports (12,21), serum-neutralizing Abs were not detected at days 14 and 28 against either A/Vietnam/1203/04 (H5N1) or A/California/07/09 (H1N1pdm09) viruses following administration of H5N1 pLAIV (Table 1).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Using a fluorescent stabilized stem immunogen (27), we determined that most, if not all, H5 + H1 + double-positive cells bound the HA stem while the H5 + single-positive cells did not (Supplemental Figure 1B). AGMs vaccinated with H5N1 pLAIV showed a small but detectable population of H5 + H1 + double-positive stem-specific memory B cells in the peripheral blood ( Figure 1, A and B) and MLNs at day 14 ( Figure 1C), but, as previously reported (21), the frequency of H5 + head-specific memory B cells was markedly higher in both the peripheral blood and MLNs at day 14 after pLAIV (0.05%-0.19% and 0.21%-0.64% for stem-and head-specific frequencies in the MLN, respectively). Consistent with these findings and our previous reports (12,21), serum-neutralizing Abs were not detected at days 14 and 28 against either A/Vietnam/1203/04 (H5N1) or A/California/07/09 (H1N1pdm09) viruses following administration of H5N1 pLAIV (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…Exploring the immunologic basis for these clinical observations in AGMs, we recently reported that intranasal administration of H5N1 pLAIV followed by matched pIIV boost generates a robust H5-specific B cell response and H5-specific neutralizing Ab response. Further, we found that H5-specific memory B cells are generated in the MLN following pLAIV (21). We did not, however, assess the ability of pLAIV to generate a broad stem-specific memory B cell pool that can be recalled upon pIIV boost.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A more comprehensive (although not exhaustive) summary of LAV attenuation mechanisms is provided in Table 2, and is associated with the following additional references: . [120,121] n/a (reassortant vaccine) [191,192] Mouse [194]; NHP [195]; Pig [196] Historical aspects of live-attenuated vaccine (LAV) creation, such as method of generation, as well as the date of the pathogen's isolation or attenuation are listed. Mechanisms of LAV attenuation are categorized into (i) genetic similarity to their parental strain or a virulent strain (with the exception of smallpox and influenza LAVs), (ii) studies on mechanisms governing LAV attenuation performed in vitro, and (iii) animal models used for in vivo investigation.…”
Section: Investigating the Molecular Mechanisms Governing Lav Attenuamentioning
confidence: 99%
“…Additional strategies employing HIV-1 related viruses [210,211] or engineered viruses harboring HIV-1 or SIV antigens [212,213] have also been tested in NHPs. NHPs have also been employed to investigate and/or evaluate the immunogenicity of many other LAVs, such as viral vectors harboring Ebola virus glycoproteins [214][215][216][217][218], LAIV [195], OPV [189,190], MV-LAV [150,185,197,[219][220][221], BCG [156], live-attenuated Venezuelan equine encephalitis virus [222], YFV-17D [151] or live-attenuated Zika virus [43]. NHP models for LAV research, however, present significant limitations.…”
Section: Of Mice Men and Non-human Primatesmentioning
confidence: 99%